The green tea polyphenol epigallocatechin-3-gallate attenuates age-associated muscle loss via regulation of miR-486-5p and myostatin - Chang, Yun-Ching; Liu, Hung-Wen; Chan, Yin-Ching; Hu, Shu-Hui; Liu, Ming-Yi; Chang, Sue-Joan (Archives of biochemistry and biophysics, 2020)
(−)-Epigallocatechin-3-gallate (EGCG), the most abundant catechin component in green tea, has been reported to attenuate age-associated insulin resistance, lipogenesis and loss of muscle mass through restoring Akt activity in skeletal muscle in our previous and present studies. Accumulated data has suggested that polyphenols regulate signaling pathways involved in aging process such as inflammation and oxidative stress via modulation of miRNA expression. Here we found that miRNA-486-5p was significantly decreased in both aged senescence accelerated mouse-prone 8 (SAMP8) mice and late passage C2C12 cells. Thus, we further investigated the regulatory effect of EGCG on miRNA-486-5p expression in age-regulated muscle loss. SAMP8 mice were fed with chow diet containing without or with 0.32% EGCG from aged 32 weeks for 8 weeks. Early passage (<12 passages) and late passage (>30 passages) of C2C12 cells were treated without or with EGCG at concentrations of 50 μM for 24h. Our data showed that EGCG supplementation increased miRNA-486-5p expression in both aged SAMP8 mice and late passage C2C12 cells. EGCG stimulated AKT phosphorylation and inhibited FoxO1a-mediated MuRF1 and Atrogin-1 transcription via up-regulating the expression of miR-486 in skeletal muscle of 40-wk-old SAMP8 mice as well as late passage C2C12 cells. In addition, myostatin expression was increased in late passage C2C12 cells and anti-myostatin treatment upregulated the expression of miR-486-5p. Our results identify a unique mechanism of a dietary constituent of green tea and suggest that use of EGCG or compounds derived from it attenuates age-associated muscle loss via myostatin/miRNAs/ubiquitin-proteasome signaling. [Display omitted] •EGCG attenuated age-associated muscle loss via upregulating miR-486-5p and modulating AKT/FoxO1/MuRF1 axis.